Balloon enteroscope-assisted endoscopic retrograde cholangiopancreatography in patients with surgically altered anatomy - Yuki Tanisaka; Masafumi Mizuide; Akashi Fujita; Tomoya Ogawa; Hiromune Katsuda; Yoichi Saito; Kazuya Miyaguchi; Ryuhei Jinushi; Rie Terada; Yuya Nakano; Tomoaki Tashima; Yumi Mashimo; et al. (Society of Gastrointestinal Intervention, 2022)
Endoscopic retrograde cholangiopancreatography (ERCP) is the gold standard for diagnosis and intervention in patients with biliopancreatic disorders. However, ERCP in patients with surgically altered anatomy (SAA) is considered more difficult than in patients with normal anatomy. Since the introduction of balloon enteroscopes for patients with small intestine disorders, single-balloon enteroscopes (SBEs) and double-balloon enteroscopes (DBEs) have also been used for biliopancreatic diseases in patients with SAA. Nevertheless, the use of conventional SBEs and DBEs is limited, as a balloon enteroscope has a working length of 200 cm and a narrow working channel with a diameter of 2.8 mm; therefore, few ERCP accessories are available for use. A short-type SBE with a working length of 152 cm and a working channel of 3.2 mm in diameter, and a short-type DBE with a working length of 155 cm and a working channel of 3.2 mm were introduced to solve these difficulties. Favorable outcomes of these devices have recently been reported. Moreover, studies have reported several tips to achieve procedural success and factors affecting procedure failure. Difficult cases necessitate alternative techniques, such as percutaneous transhepatic biliary drainage and endoscopic ultrasound-guided biliary drainage.